The Present and Possible Future of Judicial Cooperation in Civil Matters - Osztovits, András (The Policies of the European Union from a Central European Perspective, 2022)
Judicial cooperation in civil matters is based on the principle of mutual recognition, which in turn is basedon the principle of mutual trust. The study shows how the EU has been given the power to regulate this policy through the amendments to the founding treaties, what the current results of this policy are, and how the principle of mutual trust is reflected in the various EU legal sources and the relevant case law of the CJEU. It gives an overview of the most recent relevant legislation on digitization and finally suggests how to make the practical implementation of this policy in the relationship between national courts and the CJEU more effective. Keywords: principle of mutual trust, rule of law, recognition and enforcement of foreign judgments, jurisdiction, foreign service of documents, digitization, court of competent jurisdiction